Studi Alokasi Kebutuhan Air Pada Daerah Irigasi Batang Tingkarang Akibat Alih Fungsi Lahan - Andrizky Andrizky; Bambang Istijono; Ahmad Junaidi (Jurnal Pembangunan Nagari, 2017)
Batang Tingkarang Irrigation Area is an Irrigation Area authorized by West Sumatera province located in Kabupaten Pasaman with functional area of 1,419 Ha. In recent years there has been a tendency from farmers to turn their agicultural lands into fishponds. By the change of this function, hence the requirement of water will also increase, so that there is need to study about allocated water requirements at Batang Tingkarang Irrigation Area. Water demand analysis was done by comparing the dependable flow with its needs. The need for irrigation flow was analyzed by assumption that simultaneous planting season without rotation. The analysis used 8 planting alternatives and land use combinations, which were : rice-rice-rice (without fish pond), rice-rice-rice + fish, rice-rice-palawija + fish, and fish (without rice). As the results, the irrigation system was able to meet the water needs with rice-rice-rice cropping pattern if there was no land functional conversion. Excess water in this pattern can serve the land functional conversion into a fish pond with maximum of 47.99 Ha. When the cropping pattern was converted into rice-rice-palawija, the area of ​​the pond in to 169.48 Ha. By prioritizing the use of land to be converted into fish pond as much as possible, irrigation system could serve a maximum of 316.17 Ha of land functional conversion into fish ponds.